Risk factors for young people not in education, employment or training (NEET) using the Scottish Longitudinal Study - Everington, Dawn; Feng, Zhiqiang; Ralston, Kevin; Dibben, Chris (International Journal of Population Data Science, 2019)
Background The high level of young people not in education, employment or training (NEET) has been an important long-standing issue in Scotland. The experience of being NEET has long term detrimental effects. Main Aim Identify risk factors that could inform interventions aimed at reducing the number of NEETs. Methods We use the Scottish Longitudinal Study (SLS) which provides a 5.3% representative sample of Scotland’s population based around the Censuses of 1991, 2001 and 2011. The SLS includes Vital Event data, Census data for the SLS sample and also those living in the same household and, since 2007, school census data. This allows us to study two cohorts of 16-19 year olds (the ages used in Scotland when considering NEET status) over a period of 10 years: those 6-9 years old at the time of the 1991 Census to the 2001 Census when they were 16-19 years old those 6-9 years old at the time of the 2001 Census to the 2011 Census when they were 16-19 years old We used logistic regression to investigate whether NEET status is associated with individual, family and household characteristics measured 10 years previously and later data including school qualification, school behaviour, areal characteristics and teenage pregnancy. Results These analyses found several factors were associated with the likelihood of being NEET for both cohorts, including having no qualifications, teenage pregnancy and living in an area where there was a relatively high level of NEETs (100% census data). For the later cohort, school census data were available and school behaviour were important factors, whereas household characteristics at childhood were important factors for the earlier cohort. Conclusion A number of factors are associated with NEET but those closer in time to the NEET ages of 16-19 appear to be more important than childhood factors.